Novel Approach of Oxidative Coupling Reaction with 1-Naphthol of the Simultaneous Metformin Drug Determination in Either Pharmaceutics Formulations or Environmental Samples of Water Using Homemade CFIA- Merging Zones Techniques - Qassim, Bushra Basheer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A newly developed FIA-merging zones spectrophotometric system, the method is rapid, accurate and sensitive for metformin hydrochloride determination through the oxidation of 1- naphthol by sodium hypochlorite and coupling with metformin.HCl in the presence of sodium hydroxide to form a blue soluble ion pair   and this product was determined using homemade CFIA-Merging zones techniques , at 580 nm. Data treatment shows that linear range is (0.5-35) Âµg/ ml. The optimization conditions for various chemical and physical conditions of [MTF- NaOCl-Î±-naphthol-NaOH] system were investigated. The LOD was 0.01Âµg / ml and LOQ 0.1Âµg/ml from the lowest concentration of the calibration graph with r2% 99.18 and RSD% did not exceed 3%, sample through put 48 sample/h while percentage recovery (Rec.%) were from 97-100% , indicate no interferences of the tablet   excipients. The method   was applied successfully, for estimation of metformin in environmental samples of water and pharmaceutical drugs. Statistical analysis of results was compared, shows the method can be regarded as an alternative analytical way for determining of   metformin. hydrochloride in   bulk and dosage forms samples.